แผ่นเจลประดิษฐ์จากแป้งมันสำปะหลังสำหรับการประคบร้อน–เย็น - Suktanarak, Pattira; Surasartpisal, Benthiwa (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2021)
Invented Gel Pack from Cassava Starch for Hot–Cold Compress Pattira Suktanarak and Benthiwa Surasartpisal รับบทความ: 10 ธันวาคม 2563; แก้ไขบทความ: 19 มีนาคม 2564; ยอมรับตีพิมพ์: 5 พฤษภาคม 2564; ตีพิมพ์ออนไลน์: 3 ธันวาคม 2564 บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์เพื่อพัฒนานวัตกรรมแผ่นเจลจากวัสดุพอลิเมอร์ชีวภาพสำหรับการประคบร้อน–เย็น โดยใช้แป้งมันสำปะหลังเป็นสารก่อเจลร่วมกับสารเติมแต่งกลีเซอรีนและบอแรกซ์ โดยศึกษาผลของกลีเซอรีนต่อการลดการแข็งตัวของเจลที่อุณหภูมิต่ำ และผลของบอแรกซ์ต่อการคงสภาพเจลด้วยการวิเคราะห์ลักษณะทางกายภาพและโครงสร้างทางเคมีเพื่อให้ได้สูตรเจลที่เหมาะสมสำหรับประคบบนผิวหนัง และนำมาศึกษาประสิทธิภาพในการเก็บกักอุณหภูมิเปรียบเทียบกับแผ่นเจลมาตรฐานในเกรดการแพทย์ ผลการทดลองพบว่า แผ่นเจลแป้งมันสำปะหลังสามารถเก็บกักอุณหภูมิให้อยู่ในช่วงของการบำบัดได้เป็นเวลาไม่ต่ำกว่า 15–20 นาที โดยประสิทธิภาพในการเก็บกักอุณหภูมิไม่แตกต่างจากแผ่นเจลมาตรฐานในกรณีของแผ่นเจลร้อนและแผ่นเจลเย็นที่เตรียมด้วยวิธีการแช่ในอ่างน้ำแข็ง (p ³ 0.05) ขณะที่แผ่นเจลเย็นที่เตรียมด้วยการแช่ในช่องแข็งและช่องเย็นสามารถเก็บกักอุณหภูมิได้นานกว่าแผ่นเจลมาตรฐาน แต่มีความไวต่อการเปลี่ยนแปลงอุณหภูมิที่ต่ำกว่า คำสำคัญ: แผ่นเจลประคบร้อน–เย็น แป้งมันสำปะหลัง ประสิทธิภาพในการเก็บกักอุณหภูมิ Abstract This research aimed to develop a gel pack from biopolymer material for application in hot–cold compress. Our work employed cassava starch as a gelator cooperated with additive substances of glycerin and borak to improve the properties of starch gel. Our research ex-amined effect of glycerin on decreasing of gel change into the ice at low temperature, and effect of borax on stability enhancement of starch gel by analyzing physical characteristics as well as chemical structure to acquire an appropriate formula. Subsequently, the gel pack was investigated the efficiency of temperature control by comparing with standard gel in medical grade. The result showed that our starch gel can control temperature in range of clinical treatment for at least 15–20 min. In addition, efficiency of temperature control between starch gel and standard gel was no difference in case of hot gel as well as cold gel preparing in ice bath (p > 0.05). On the other hand, our cold gel prepared by freezing and cold storage exhibited a performance of temperature control higher than standard gel, but it was lower sensitivity to temperature. Keywords: Hot–cold gel pack, Cassava starch, Efficiency of temperature control